Knowledge, attitudes, and practices of nurses towards hand washing in infection prevention and control at a psychiatric hospital - M. Bimerew; F. Muhawenimana (International Journal of Africa Nursing Sciences, 2022)
The study examined the knowledge, attitudes and practices of nurses towards compliance with hand washing in a selected psychiatric hospital. A descriptive survey design with self-administered questionnaire was used to collect data from 195 nurses. The study population comprised all categories of nurses (registered nurses, enrolled nurses, auxiliary nurses, enrolled nurse assistants) permanently employed at the selected psychiatric hospital. The results show a discrepant levels of knowledge, attitudes and hand washing practices between genders, with males having slightly more knowledge (mean score 92.5) than females (mean score 91.41); female nurses had a better attitude (mean score 96.06) than male nurses (mean score 95.09), and a higher level of hand washing practice (mean score 95.63) than male nurses (mean score 94.66). There was no statistically significant association between gender and attitudes of nurses towards hand washing (P = 0.42). Registered nurses had slightly more knowledge and positive attitudes than the other categories of nurses. Educational level had an impact on knowledge of hand washing, but less impact on attitudes and practices. No statistically significant association was found between demographic variables and knowledge, attitudes and practices on hand hygiene. The study demonstrated knowledge gaps among respondents about various aspects of hand hygiene. Variations in attitude level were noted among nurses in terms of age, gender, rank, work experience and educational level. Moreover, it was noted that there was possible overestimation of hand hygiene practice and knowledge by the respondents. Continuous monitoring and evaluation should be put in place with the aim of translating knowledge into action, changing attitudes into positive behaviour, and promoting/maintaining correct hand washing techniques. This is crucial to maintain standards in level of knowledge and attitudes and consistent correct practices of hand washing procedures throughout nurses’ professional lives in infection prevention and control at a psychiatric hospital.